ASSESSMENT OF TECHNOLOGICAL AND ENVIRONMENTAL RISK ACCORDING TO THE CRITERIA OF ENVIRONMENTAL AND ECONOMIC EFFICIENCY OF COAL MINING ENTERPRISES OF THE DONTSK AND LUHANSK REGIONS - ULYTSKYI, Oleg; KURYLO, Mariia; BALA, Volodymyr (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The peculiarities of the geological and technical conditions of the coal deposits of the Donetsk coal basin, which are concentrated within the Donetsk and Luhansk regions, are revealed. The main indicators are given and an analysis of the technical and economic state of the coal industry is performed using the example of the main coal mining enterprises of the studied territories. An assessment of the complex impact on the surrounding natural environment сreated by the main coal-mining enterprises was carried out, based on a detailed examination and identification of a number of factors of the creation of man-made load within the limits of technology technical complexes of coal mining facilities. The assessment of technogenic and environmental risk based on the criteria of ecological and economic efficiency of coal mining enterprises of Donetsk and Luhansk regions made it possible to form the first approximate, but scientifically based ideas about the profitability (unprofitability) of coal mining activities of some enterprises, which is the basis for the further development of recommendations on consistency and expediency closing of mines in order to reduce the technogenic load. The article analyzes and uses data from the official environmental reporting of coal-mining enterprises, data from the Geoinform Ukrainy State Research Institute, the Ministry of Energy, the State Statistics Service, and scientific and methodological sources. According to the results of the assessment of the parameter of ecological and economic efficiency of enterprises and analysis of its influence on the formation of ecological safety of production, none of the main coal-mining enterprises of Donetsk and Luhansk regions is considered ecologically safe. Enterprises of SE "Lysychanskvugilya", SE "Pervomaiskvugilya" (Luhansk region), as well as enterprises of SE "Myrnogradvugilya" and SE "Selydivvugilya" (Donetsk region) are characterized by the lowest value of the coefficient of optimality of technological processes and are classified as extremely environmentally dangerous enterprises according to the results of the assessment.